(3TQM GdaQGFV GdSLGhfOjIs - (3GdLQLGfj, Ydj Hf eMeO Hf Ydj, GdeYQha HGdTQja GdLQLGfj J (B816 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; bGd eMeO Hf YHO GdQTjO GdSLGhfOj HYO eG Jjef HGdJSejI GdMeO ddg QH GdYGdejf hMeO GdTGcQjf bGd QShd Gddg Udi Gddg Ydjg hSde (B" (3JYdehG GdaQGFV hYdehgG GdfGS(B" (3h GdaQGjV LeY aQjVIs
(3BNQgG (B:s
(3SJI hKdGKhf hYdi JbOjQ CfhKJg ddeQCI CQHYI hYTQhf dGf SgGegG ef eSCdI GdCfhKI CYfj SHYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 7s
(3eYLe GdeDdajf (B2 / 514 (3, (B515s
(3cTa GdXfhf (B2 / 12487s
(3gOjI GdYGQajf (B1 / 728s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdaQGFVs